Liquid-liquid phase separation and core-shell structure of ternary Al-In-Sn immiscible alloys. (11th April 2018) - Zhao, Degang; Bo, Lin; Wang, Lin; Li, Shanshan
Abstract: In this study, the liquid-liquid phase separation of four kinds of ternary immiscible Al-In-Sn melts was investigated with resistivity and thermodynamics method. The nonlinear changes in ρ -T and DSC curves of Al-In-Sn immiscible alloys above monotectic reaction temperature revealed the occurrence of liquid-liquid phase separation of Al-In-Sn melts. The monotectic temperature, liquid phase separation temperature and immiscible gap of ternary Al-In-Sn alloys were lower than those of binary Al-In alloy. With the Al content decreasing, the immiscible gap of Al-In-Sn alloy decreased. The composition of Al80 In10 Sn10, Al70 In15 Sn15, Al60 In20 Sn20 and Al50 In25 Sn25 was located in the immiscible zone of Al-In-Sn system. Due to the differences of Stokes effect, Marangoni convection and immiscible gap, the solidification morphology of four kinds of Al-In-Sn monotectic alloy was different. The core–shell structure of Al-In-Sn monotectic alloy can form within a certain range of composition.